Constructive and destructive interference of Kerker-type scattering in an ultrathin silicon Huygens metasurface - Bradley, Louise; Donegan, John (My University, 2020)
High refractive index dielectric nanoparticles have provided a new platform for exotic light manipulation through the interference of multipole modes. The Kerker effect is one example of a Huygens source design. Rather than exploiting interference between the electric dipole and magnetic dipole, as in many conventional Huygens source designs, we explore Kerker-type suppressed backward scattering mediated by the dominant electric dipole, toroidal dipole, and magnetic quadrupole. These modes are provided by a designed and fabricated CMOS compatible ultrathin silicon nanodisk metasurface with a suppressed magnetic dipole contribution and verified through multipole decomposition. The nontrivial substrate effect is considered using a semianalytical transfer matrix model. The model successfully predicts the observed reflection dip. By applying a general criterion for constructive and destructive interference, it is shown that while constructive interference occurs between the electric and toroidal dipole contributions, the experimentally observed suppressed backward Kerker-type scattering arises from the destructive interference between backward scattered contributions due to the electric dipole and the magnetic quadrupole. Our study paves the way towards new types of Huygens sources or metasurface design, such as for peculiar transverse Kerker scattering.
PUBLISHED
Keywords: Interference and diffraction of light; Mie scattering; Scattering theory